Economics - Mankiw, N. Gregory (South-Western Cengage Learning, 2012)
Part 1: Introduction. Ten Principles of Economics ; Thinking Like an Economist ; Interdependence and the Gains from Trade. -- Part 2: How markets work. The Market Forces of Supply and Demand ; Elasticity and Its Application ; Supply, Demand, and Government Policies. -- Part 3: Markets and welfare. Consumers, Producers, and the Efficiency of Markets ; Applications: The Costs of Taxation ; Application: International Trade. -- Part 4: The economics of the public sector. Externalities ; Public Goods and Common Resources ; The Design of the Tax System. -- Part 5: Firm behavior and the organization of industry. The Costs of Production ; Firms in Competitive Markets ; Monopoly ; Monopolistic Competition ; Oligopoly. -- Part 6: The Economics of the labor market. The Markets for the Factors of Production ; Earnings and Discrimination ; Income Inequality and Poverty. -- Part 7: Topics for further study. The Theory of Consumer Choice ; Frontiers in Microeconomics. -- Part 8: The data of macroeconomics. Measuring a Nation's Income ; Measuring the Cost of Living. -- Part 9: The real economy in the long run. Production and Growth ; Saving, Investment, and the Financial System ; Tools of Finance ; Unemployment and Its Natural Rate. -- Part 10: Money and prices in the long run. The Monetary System ; Money Growth and Inflation. -- Part 11: The macroeconomics of open economics. Open-Economy Macroeconomics: Basic Concepts ; A Macroeconomic Theory of the Open Economy. -- Part 12: Short-run economic fluctuations. Aggregate Demand and Aggregate Supply ; The Influence of Monetary and Fiscal Policy on Aggregate Demand ; The Short-Run Tradeoff between Inflation and Unemployment. -- Part 13: Final thoughts. Six Debates over Macroeconomic Policy.; Includes bibliographical references and index